(untitled) (BISTUA Revista de la Facultad de Ciencias Básicas, 2022)
The mitotic index percentage bioassay in Allium cepa is currently used in various fields of science and industry to determine the cytotoxic potential of multiple compounds, due to its high sensitivity, because it is easy to access, economical and because of its practicality in the moment to do it. In the present study, this mitotic index percentage was determined under specific growth conditions of the root meristem A. cepa (growth time of 4 days, tap water changed twice a day, temperature between 20 and 22 ° C to compare it with previous studies and observe the variability or similarity of the results. It was established that the mitotic percentage under the experimental conditions for this trial was 14.92 SD±1.18, which is consistent with reported studies, but there is also variability in the data that may be due to the fact that the percentage of mitotic index may be influenced by the development conditions of the A. cepa meristem such as the type of water in which the bulb grows, the root growth time, the photoperiod, temperature and physiological state of the onion bulb. In conclusion, the percentage of mitotic index obtained presents a minimal difference with other studies, being an effective model for in vitro replication of antimitotic activity.